The flash-preview moving window paradigm: Unpacking visual expertise one glimpse at a time - Litchfield, Damien; Donovan, Tim (Frontline Learning Research, 2017)
How we make sense of what we see and where best to look is shaped by our experience, our current task goals and how we first perceive our environment. An established way of demonstrating these factors work together is to study how eye movement patterns change as a function expertise and to observe how experts can solve complex tasks after only very brief glances at a domain-specific image. The primary focus of this paper is to introduce an innovative gaze-contingent method called the ‘Flash-Preview Moving Window’ (FPMW) paradigm (Castelhano & Henderson, 2007), which was recently developed to understand our shared expertise in scene perception and how our first glimpse of a scene is used to guide our eye movement behaviour. In keeping with this special issue on visual expertise and medicine, this paper will highlight how the FPMW paradigm has the potential to resolve long-standing theoretical issues as to how, right from the very first glance, experts are able to process domain-specific images and guide their eye movements better than novices. Since FPMW is a gaze-contingent eye-tracking method, the paper will first outline the current methodological and theoretical frontier, and how the FPMW paradigm bridges established methods used to investigate visual expertise. The paper will discuss a recent example in which the FPMW was employed to investigate medical image perception expertise for first the time (Litchfield & Donovan, 2016), and by confronting the insights and challenges this method offers, this should ultimately deepen our understanding of visual expertise.